Адміністративно-правові засади та напрямки взаємодії Державного бюро розслідувань України з іншими державними органами та громадськістю у правоохоронній сфері в умовах воєнного стану - Казанчук, І. Д.; Kazanchuk, I. D.; Казанчук Ірина Дмитрівна (Європейські перспективи. - 2024. - № 1. - С. 32-37, 2024)
У статті досліджено сучасний стан адміністративно-правового регулювання взаємодії підрозділів Державного бюро розслідувань України з іншими органами державної влади та громадськістю у сфері виконання правоохоронної функції держави. Спираючись на норми національного законодавства та аналіз теоретичних поглядів, визначено поняття «взаємодії», її видів у діяльності Державного бюро розслідувань. Зроблено висновок про необхідність на законодавчому рівні закріплення поняття форм, видів та меж взаємодії ДБР з іншими державними органами і громадськістю з метою покращення діяльності ДБР у правоохоронній сфері.

The article examines the current state of administrative and legal regulation of interaction between the units of the State Bureau of Investigation of Ukraine and other public authorities and the public in the area of law enforcement function of the State. Based on the provisions of national legislation and the analysis of theoretical views, the author defines the concept of «interaction» and its types in the activities of the State Bureau of Investigation. Taking into account of the State Bureau of Investigation of Ukraine powers and tasks, as well as the provisions of the Strategic Program of the State Bureau of Investigation for 2022- 2026, the main areas of its interaction with other state bodies and public institutions are outlined. These types of interaction include: 1) exchange of operational information, its transfer to other state agencies within their competence; 2) conclusion of agreements (memorandums) on cooperation and exchange of information with individual state agencies; 3) information and analytical interaction; 4) cooperation in the field of prevention and counteraction to corruption, legalization (laundering) of proceeds from crime, strengthening of control over the use of the State Budget of Ukraine; 5) interaction to identify the facts of torture and ill-treatment of people; 6) organization of preventive measures to prevent criminal acts. The author analyzes the implementation of each of these forms of interaction of the State Bureau of Investigation of Ukraine. The author concludes that it is necessary to enshrine at the legislative level the concept of forms, types and limits of interaction between the State Bureau of Investigation of Ukraine and other state authorities and the public in order to improve the State Bureau of Investigation activities in the law enforcement sphere.

Исследовано современное состояние административно-правового регулирования взаимодействия подразделений Государственного бюро расследований Украины с другими органами государственной власти и общественностью в сфере выполнения правоохранительной функции государства. Опираясь на нормы национального законодательства и анализ теоретических взглядов, определено понятие «взаимодействия» ее видов в деятельности Государственного бюро расследований. Сделано заключение о необходимости на законодательном уровне закрепления понятия форм, видов и границ взаимодействия ДБР с другими государственными органами и общественностью с целью улучшения деятельности ДБР в правоохранительной сфере.
Administrative and legal principles and directions of interaction of the State Bureau of Investigations of Ukraine with other state bodies and the public in the law enforcement sphere under martial law
Keywords: Державне бюро розслідувань України; правове регулювання; взаємодія; форми; правоохоронна діяльність; державні органи; організація; громадськість; State Bureau of Investigation of Ukraine; legal regulation; interaction; forms; law enforcement; state bodies; organization; public; Государственное бюро расследований Украины; правовое регулирование; взаимодействие; формы; правоохранительная деятельность; государственные органы; организация; общественность